2017
DOI: 10.1007/s12253-017-0370-8
|View full text |Cite
|
Sign up to set email alerts
|

Data on Single Nucleotide Polymorphism of DNA Repair Genes and Breast Cancer Risk from Poland

Abstract: Single nucleotide polymorphisms (SNPs) may modify the risk of cancer. They may be then regarded as potential markers of carcinogenesis. The aim of this study was to analyze the frequency of genotypes and alleles of SNPs in DNA repair genes and to investigate the influence this genetic variation exerts on breast cancer in Polish females. The test group comprised 600 females with breast cancer and 600 healthy controls. Genomic DNA was isolated and the SNPs in DNA repair genes were determined by High-Resolution M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…While the Gln allele of rs25487 leads to a reduction in BER DNA repair activity [24]. Also in this case, the results about the frequency of genotypes of XRCC1-rs1799782 (Arg to Trp) and rs25487 (Arg to Gln) and the BC susceptibility are contrasting [21,[68][69][70][71][72][73][74][75][76][77]. In our study, the XRCC1-rs25487 polymorphism is nominally associated with family history of BC in two genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…While the Gln allele of rs25487 leads to a reduction in BER DNA repair activity [24]. Also in this case, the results about the frequency of genotypes of XRCC1-rs1799782 (Arg to Trp) and rs25487 (Arg to Gln) and the BC susceptibility are contrasting [21,[68][69][70][71][72][73][74][75][76][77]. In our study, the XRCC1-rs25487 polymorphism is nominally associated with family history of BC in two genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses carried out in 2014 (Qin et al, 2014) and 2017 (Miao et al, 2017) reported no association of the p.Pro871Leu polymorphism and breast cancer risk. Contradictory results have also been reported for the BRCA1 871L allele, as significantly associated with increased risk of breast cancer in a Polish population (Smolarz et al, 2017). An association of the TT genotype with reduced breast cancer risk in Chinese has also been reported (Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 80%
“…Maertens and co-workers additionally showed an effect on reduction of MMR activity. In more recent studies, re4987188 was also associated with increased risks to vestibular schwannoma (odds ratio (OR) 1.67), recurrent colon cancer, lung cancer (OR 1.29), and breast cancer (OR 10.61) clearly attributed to the A allele in most studies [16,[63][64][65]. From current data, it can therefore be concluded that the A allele, being detected only in NF1 patients with a high tumour burden, serves as a disease modifier towards an increased neurofibroma load.…”
Section: Non-pathogenic Msh2 Variants and Neurofibroma Manifestationmentioning
confidence: 99%